2015
DOI: 10.1016/j.sbspro.2015.04.204
|View full text |Cite
|
Sign up to set email alerts
|

Soft Skills Integration in Teaching Professional Training: Novice Teachers’ Perspectives

Abstract: This paper is part of a bigger research project and focuses on issues related to soft skills and teaching professional training. The research project is on developing an integrated soft skills training module for teacher education program in Malaysian Public Universities. The purpose of this paper is to explore the extent of soft skills that has been integrated in teaching professional training from the novice teachers' perspectives. The issues of unemployment and lack of quality among teachers are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 4 publications
5
38
0
8
Order By: Relevance
“…Giving self-duty or individual project was a method used by the lecturers to train the attitude of self-reliance and responsibility of TPEP students. This was very reasonable because integrating soft skills into the curriculum did not mean that there was a new topic added in the teaching curriculum, rather the soft skills that would be trained could be embedded in tasks or projects related to existing subject matters (Tang, Yunus, & Hashim, 2015). For a teacher, independence and a sense of responsibility were things that needed to be demonstrated in performing his or her tasks at school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving self-duty or individual project was a method used by the lecturers to train the attitude of self-reliance and responsibility of TPEP students. This was very reasonable because integrating soft skills into the curriculum did not mean that there was a new topic added in the teaching curriculum, rather the soft skills that would be trained could be embedded in tasks or projects related to existing subject matters (Tang, Yunus, & Hashim, 2015). For a teacher, independence and a sense of responsibility were things that needed to be demonstrated in performing his or her tasks at school.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of soft skills is important for pre-service teachers, especially to make their pedagogical practices effective. However, the facts have shown that soft skills possessed by teachers were still low (Fadli & Irwanto, 2020;Tang, Yunus, & Hashim, 2015). The low proficiency of the teachers' soft skills is often demonstrated by the less effective learning management performed by the teachers.…”
Section: Research Problemmentioning
confidence: 99%
“…The level of individual achievement is assessed through self-evaluation [45]. The study conducted by Ngang et al (2014) showed that teachers recognise the importance of soft skills in the teaching profession, but at the same time feel insufficiently prepared in this regard [46].…”
Section: Self-managementmentioning
confidence: 99%
“…The universities introduce soft skills components and integrate them into syllabus. In the veterinary carrier, along with specific skills, veterinarians need to have communicative competence, critical thinking, visual thinking, team working, ICT skills, social intelligence, intercultural abilities [1,2]. Stand-alone subjects provide students with opportunities to develop soft skills on a formal base.…”
Section: Introductionmentioning
confidence: 99%